Characterization of strongly coupled plasmas produced in argon supercritical fluids. (1st September 2022) - Lee, Seungtaek; Lee, Juho; Yoon, Young Dae; Kim, Dong Eon; Yun, Gunsu
Abstract: Strongly coupled plasmas (SCPs) exist in various places throughout the Universe, examples of which are inertial confinement fusion experiments, Jovian planets' cores, neutron stars, and white dwarf stars. In recent decades, theoretical and numerical studies have been pursued to characterize the equation of states and thermodynamic properties of SCPs, which are fundamentally different from those of weakly coupled plasmas. One of the essential research topics is energy transport by radiation or opacity. In particular, in a subcritical medium at a low temperature, condensation renders the medium inhomogeneous, which significantly affects the radiation transport or opacity. However, no study has been conducted for opacity in inhomogeneous supercritical fluids (SCFs). A recent study reveals that an inhomogeneous SCF with nanometer-sized clusters and micrometer-sized droplets can be prepared. Here, we experimentally demonstrate that the emission timescale of an SCP in an inhomogeneous SCF is extended by up to 50% compared to that in a homogeneous SCF. This implies that the inhomogeneity of the SCF significantly enhances the photon confinement. This result is expected to draw interest in the investigation of radiation transport or opacity in the inhomogeneous SCF. A better understanding will lead to a method for increasing the brightness and light emission time from a dense plasma.